2014
DOI: 10.1186/1750-2187-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box O1 and muscle RING finger 1 protein expression in atrophic and hypertrophic denervated mouse skeletal muscle

Abstract: BackgroundForkhead box O (FoxO) transcription factors and E3 ubiquitin ligases such as Muscle RING finger 1 (MuRF1) are believed to participate in the regulation of skeletal muscle mass. The function of FoxO transcription factors is regulated by post-translational modifications such as phosphorylation and acetylation. In the present study FoxO1 protein expression, phosphorylation and acetylation as well as MuRF1 protein expression, were examined in atrophic and hypertrophic denervated skeletal muscle.MethodsPr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The upstream FoxO transcription factors FoxO1 and FoxO3 are involved in the regulation of muscle mass and atrophy. 15,19,[48][49][50] We found that both FoxO1 and FoxO3 were significantly upregulated within 3 days of crush injury, but the significant effect of 4-AP treatment on the FoxO expression levels was evident only at day 7, and it was more pronounced on FoxO3. Although FoxO3 activation alone has been reported to be sufficient to cause significant muscle atrophy in vivo, 15,19 FoxO members are redundant in their function, and both FoxO1 and FoxO3 participate in muscle atrophy.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The upstream FoxO transcription factors FoxO1 and FoxO3 are involved in the regulation of muscle mass and atrophy. 15,19,[48][49][50] We found that both FoxO1 and FoxO3 were significantly upregulated within 3 days of crush injury, but the significant effect of 4-AP treatment on the FoxO expression levels was evident only at day 7, and it was more pronounced on FoxO3. Although FoxO3 activation alone has been reported to be sufficient to cause significant muscle atrophy in vivo, 15,19 FoxO members are redundant in their function, and both FoxO1 and FoxO3 participate in muscle atrophy.…”
Section: Discussionmentioning
confidence: 66%
“…In line with RT‐PCR data, results of Western blot analysis in muscle homogenates confirmed the role of 4‐AP in restoring myogenin levels in affected muscle after sciatic nerve crush injury. The upstream FoxO transcription factors FoxO1 and FoxO3 are involved in the regulation of muscle mass and atrophy . We found that both FoxO1 and FoxO3 were significantly upregulated within 3 days of crush injury, but the significant effect of 4‐AP treatment on the FoxO expression levels was evident only at day 7, and it was more pronounced on FoxO3.…”
Section: Discussionmentioning
confidence: 76%
“…The expression of atrogin-1 and MuRF1 is regulated by FOXO transcription factors, especially FOXO1 and FOXO3 [27,28]. Indeed, the protein levels and activities of FOXO1 and FOXO3 are increased in the atrophic skeletal muscles of mice [29,30]. Furthermore, the overexpression of FOXO proteins was shown to increase atrogin-1 mRNA levels and induce skeletal muscle atrophy, whereas FOXO deficiency prevented skeletal muscle atrophy [27,31].…”
Section: Discussionmentioning
confidence: 94%
“…A synthetic glucocorticoid, dexamethasone (DEX), induces muscle atrophy, which involves both induction of protein degradation and suppression of general protein synthesis [ 2 ]. Recent studies show that two muscle-specific E3 ubiquitin ligases, atrogin-1/muscle atrophy F-box (atrogin-1) and muscle ring finger protein 1 (MuRF-1), the so-called atrogenes [ 3 ], play key roles in muscle atrophy caused by immobilization and denervation [ 4 , 5 ], as well as DEX treatment [ 6 ]. Furthermore, their gene expression and activities are regulated by transcription factors from the class O type forkhead (Foxo) family [ [4] , [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%